2019
DOI: 10.1016/j.celrep.2019.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Calcineurin Signaling Restrains Metastatic Outgrowth by Regulating Bmp2

Abstract: Highlights d Endothelial calcineurin is dispensable for physiological and tumor angiogenesis d Endothelial calcineurin stabilizes vessels and restrains metastatic outgrowth d Calcineurin/NFAT target BMP2 induces differentiation of metastatic cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…We have shown that biglycan, a small leucine-rich repeat proteoglycan, was remarkably upregulated in TECs and facilitated the migration of toll-like receptor-expressing tumor cells, which increased circulating tumor cells and lung metastasis [79]. Endothelial calcineurin have a unique function, which does not affect primary tumor growth, but activates the outgrowth of metastases [99]. These studies suggested that TECs actively promote tumor cell progression and metastasis.…”
Section: The Role Of Tecs In Cancer Progressionmentioning
confidence: 99%
“…We have shown that biglycan, a small leucine-rich repeat proteoglycan, was remarkably upregulated in TECs and facilitated the migration of toll-like receptor-expressing tumor cells, which increased circulating tumor cells and lung metastasis [79]. Endothelial calcineurin have a unique function, which does not affect primary tumor growth, but activates the outgrowth of metastases [99]. These studies suggested that TECs actively promote tumor cell progression and metastasis.…”
Section: The Role Of Tecs In Cancer Progressionmentioning
confidence: 99%
“…During the process of bone defects repair, the angiogenesis is complicated and cascading procedure, which involves the extracellular matrix degradation and forming, cell adhesion, proliferation, migration, and morphological differentiation of endothelial cells to form capillary tube [9,10]. The initiation of the complex procedure relies on the stimulation of some pro-angiogenic factors, such as vascular endothelial growth factor (VEGF), stromal cell-derived factor 1(SDF-1), and bone morphogenetic proteins 2 (BMP2, [11][12][13][14]). Among these pro-angiogenic factors, BMP2 plays an important role.…”
Section: Introductionmentioning
confidence: 99%
“…RNA sequencing was done as has been previously described (63, 64); details are outlined in SI Appendix , SI Materials and Methods .…”
Section: Methodsmentioning
confidence: 99%